Islamic Journalism and the Challenges of Objectivity - Ilyas, Sanusi; Xiang, Yang; Wei, Sun (Journal International Dakwah and Communication, 2024)
Islamic journalism operates within a framework that integrates ethical and religious principles, presenting distinct challenges in maintaining objectivity. The tension between upholding journalistic neutrality and adhering to Islamic ethical guidelines raises questions about bias, credibility, and professional standards in Islamic media practices. This study aims to analyze the complexities of objectivity in Islamic journalism by examining its theoretical foundations, ethical boundaries, and practical applications in contemporary media landscapes. Employing a qualitative approach, this research utilizes content analysis and in-depth interviews with journalists from various Islamic media outlets. The findings reveal that while Islamic journalism strives for truthfulness and fairness, it often navigates ideological influences and societal expectations that shape reporting styles. Additionally, structural limitations, editorial policies, and political factors further challenge the realization of absolute objectivity. This study concludes that while complete neutrality may be unattainable, Islamic journalism can enhance credibility by promoting balanced reporting, ethical transparency, and adherence to professional journalism standards. These insights contribute to the discourse on media ethics, highlighting the need for frameworks that align Islamic values with universal journalistic principles.